TREN PENELITIAN MAHASISWA PENDIDIKAN BIOLOGI UIN WALISONGO SEMARANG TAHUN 2020-2023 - Erna Wijayanti; nurhalimah, sevira (Center of Education Journal (CEJou), 2023)
The purpose of this investigation is to determine the research trends of biology education students at UIN Walisongo Semarang. The type of research employed is a qualitative literature review. The research was conducted in the library of UIN Walisongo Semarang between April and May of 2023. 38 theses written by biology education students at UIN Walisongo Semarang's campus library served as the study's subjects. The technique used for data collection was a systematic document analysis of thesis documents. In addition, researchers classified the type of research conducted and presented it in tabular format after obtaining an overview with an abstract analysis and research methodology. The research instrument used was a category sheet. The technique used for data analysis is descriptive-quantitative. The sample information will be analyzed using a category sheet. Based on the results of the category sheet analysis, the research trend of UIN Walisongo Semarang students during the period 2020–2023 is quantitative research; the most popular type of research is R&D research, with a high school research sample trend.